Integrating Ibn Khaldun and Ki Hajar Dewantara for Teacher Professional Development and Student-Centered Learning Management in Islamic Education - Sa'adah, Miftahus; Sulistiyo, Rozib (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines the integration of Ibn Khaldun’s and Ki Hajar Dewantara’s educational concepts for teacher professional development and student-centered learning management in Islamic education. It used a qualitative comparative literature review by analyzing scholarly books, journal articles, and curriculum-related studies. Data were processed through open coding, axial coding, thematic comparison, and integrative synthesis. The findings show that Ibn Khaldun emphasizes the integration of religious and rational knowledge, moral habituation, staged learning, teacher exemplarity, and social responsibility. Ki Hajar Dewantara emphasizes learner autonomy, cultural relevance, educational collaboration, and holistic learning through Among, Tri Sentra Pendidikan, Tri Nga, and Pancadarma. Their integration produces a framework that positions teachers as moral exemplars, facilitators, mentors, and learning managers. It also supports value-based curriculum management, reflective and experiential learning, school-family-community collaboration, and institutional quality culture. The study concludes that combining Khaldun’s ethical-intellectual orientation with Dewantara’s humanistic and culturally grounded pedagogy provides a relevant foundation for Islamic education management that balances academic competence, character formation, student autonomy, and social responsibility.